Effects of equivalence ratio on vented H2/CH4/air explosions in the chamber with a hinged vent panel - Hongzhe Rong; Jialin Li; Jin Guo; Yiming Wang; Zhongrui Chen; Fuqiang Yang (Fuel, 2026)

Iron-amidoximated polyacrylonitrile fiber catalyst with high intrinsic peroxidase-like activity for efficient and durable degradation of organic pollutants - Bingbing Chen; Huaixiang Lv; Sheng Guo; Rong Chen; Fengxi Chen (Chemical Engineering Journal, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

Orders-of-magnitude reactivity enhancement in persulfate activation by curvature-dependent oxygenated carbon nanotubes - Xin Yang; Zhongyuan Guo; Pufan Wang; Justin Prabowo; Yangyang Wang; Jiaxiang Chen; Jiacheng Wu; Xinyi Huang; Yichen Feng; Chengli Rong; Fangzhou Liu; Hao Li; et al. (Chemical Engineering Journal, 2026)

A new antibacterial unsaturated fatty acid from Xisha coral-associated actinomycete Streptomyces sp. SHEa3 - Rong Wang; Shiquan Chen; Quanying Feng; Zhikai Guo; Qiuhua Mao (Phytochemistry Letters, 2026)

Integrated metabolomics and network pharmacology reveal metabolic remodeling and potential antioxidant mechanisms in fermented Lycium barbarum - Jianyu Huang; Dengmi Wang; Ziyi Yang; Jinrou Xie; Die die Wang; Rong Guo; Dunhua Liu; Song Miao; Jicheng Chen (Food Bioscience, 2026)

Persistent contamination, limited accumulation: In-situ isotope tracing reveals fast thallium turnover in natural waters - Chenghong Yu; Hongkai Wang; Wenze Xiao; Qiao-Guo Tan; Rong Chen; Lihua Liu; Nengwang Chen; Minwei Xie (Aquatic Toxicology, 2026)

Enzymatic Preparation of Ejiao (Colla Corii Asini) Peptides and Their Preliminary Mechanism of Melanogenesis Inhibition - Xichao Fu; Shangwei Guo; Meijin Li; Zhijie Chen; Dan Liu; Cuicui Men; Na Yang; Xiaobo Duan; Xiaolu Tang; Yaru Zhang; Haibin Liu; Minghao Liu; et al. (International Journal of Peptide Research and Therapeutics, 2026)

Effect of dissolved organic matter chemical characters on microbial community of paddy soils in subtropical China - Yaxin Liu; Yingcong Ye; Daming Li; Rong Cui; Xiaoli Liu; Ling Chen; Meng Wu; Jia Liu; Xi Guo; Ming Liu (Soil and Tillage Research, 2026)

Corrigendum to ‘Machine Learning-Driven Recombinant Xylanase Synergized with Pediococcus pentosaceus: Directed Xylose-Lactate Conversion and Metabolic Mechanism of Lignocellulosic Waste’[Resources, Conservation & Recycling 234 (2026) Article 109058] - Jiajin Sun; Yujuan Zhang; Luyao Zhang; Chen Shen; Yitong Lin; Rong Zhao; Lei Chen; Qiang Liu; Cong Wang; Wenjie Huo; Gang Guo (Resources, Conservation and Recycling, 2026)

Inoculation with phosphate-solubilizing bacteria reduce the transport of cadmium in Brassica napus L. by reshaping phosphate-solubilizing microbes in rhizosphere - Xiao Chen Zhang; Tong Yu Feng; Xiu Rong Tao; Lu Chen Wang; Jing Wen Kong; Yi Yao Mai; Yang Chen; Qing Guo; Long Guo; Chuan Jun Dai; Min Zhao (Rhizosphere, 2026)

Temporal modulation of acidification, volatile aroma profiles and sensory attributes during lactic acid bacteria fermentation of Berliner Weisse - Bo-Jun Liao; Huei-Rong Guo; Chun-Neng Huang; Chen-Che Hsieh (Food Bioscience, 2026)

In-situ generation and activation of H2O2 by synergistic dipole moment and multi-metal cycle for piezo-photocatalytic water cleanup - Zheng-Tao Dong; Long Sui; You Wu; Xiao-Ju Wen; Ya-Ya Yang; Yan-Rong Chen; Wen-Jun Wang; Hai Guo (Chemical Engineering Journal, 2026)

Cinnamoylphenethyl amides from fissistigma bracteolatum and their anti-inflammatory activities - Jin-Feng Xue; Yao-Yao Jia; Jing-Wei Lei; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhen-Zhu Zhao; Dong-Rong Zhu; Guo-Sheng Li; Gui-Min Xue (Natural Product Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Machine learning-driven recombinant xylanase synergized with Pediococcus pentosaceus: directed xylose-lactate conversion and metabolic mechanism of lignocellulosic waste - Jiajin Sun; Yujuan Zhang; Luyao Zhang; Chen Shen; Yitong Lin; Rong Zhao; Lei Chen; Qiang Liu; Cong Wang; Wenjie Huo; Gang Guo (Resources, Conservation and Recycling, 2026)

Spatiotemporal characteristics and influencing factors of phosphorus metabolism in China's food consumption and disposal system - Shenyi Lu; Zheng Guo; Sophia Shuang Chen; Xingchun Cen; Rong Li; Giri Raj Kattel (Journal of Cleaner Production, 2026)

Reducing environmental footprints of food consumption in urban and rural China: A scenario-based optimization towards sustainable diets - Zheng Guo; Junjie Zhao; Sophia Shuang Chen; Jialong Xu; Yi Zhang; Rong Li; Yingyi Ma; Enkang Li; Giri Raj Kattel (Journal of Environmental Management, 2026)

MOF-derived carbon composites: Magnetically induced high electromagnetic shielding effectiveness and intelligent regulation of absorption-dominated mechanism - Lin Chen; Yujun Rong; Xin Zhou; Xiyu Qiu; Xiaofan Ma; Shaohua Jiang; Jianzhong Guo (Chemical Engineering Journal, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

From gas-liquid to liquid-liquid: A programmable compartmented droplet microreactor under ambient conditions - Gaojian Chen; Duo Wei; Junhao Zhu; Rong Guo; Lingling Ge (Chemical Engineering Journal, 2026)

Interfacial engineering of 2D heterojunction with coordination bridging for efficient photocatalytic biomass upgrading - Taolian Guo; Rong Dang; Shaodan Wang; Anyu Zheng; Wu Chen; Chao Wang (Chemical Engineering Journal, 2026)

Occurrence characteristics and ecological risk assessment of microplastics in the water body of lake Gahai, Tibetan Plateau of China - Guo-hong Wu; Yan-rong Tan; Wen-ye Chen (Environmental Geochemistry and Health, 2026)

Multidimensional effects of digital inclusive finance toward carbon emissions in agriculture: empirical evidence from 31 Chinese Provinces - Jiancheng Zheng; Liang Chen; Shangjia Guo; Rong Niu; Peibin Chen (Environment, Development and Sustainability, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Novel prenylated diketopiperazines with anti-osteoclastogenic activity from the deep-sea-derived Penicillium limosum ZEN48 - Yong Zhang; Yan-Qing Guo; You Li; Zheng-Biao Zou; Zhe-Wen Chen; Rong Zhao; Robert J. Capon; Tai-Zong Wu; Chun-Lan Xie; Xian-Wen Yang (Marine Life Science & Technology, 2026)
A systematic chemical investigation of the deep-sea-derived fungus Penicillium limosum ZEN48 resulted in the isolation of four new indole-diketopiperazine alkaloids, limopiperazines A–D ( 1 – 4 ), alongside 16 known analogues ( 5 – 20 ). The structures of the new compounds were determined through comprehensive spectroscopic analysis, quantum chemical calculations, X-ray crystallography, and biogenetic considerations. Limopiperazine C ( 3 ) potently inhibited osteoclast differentiation and disrupted actin ring formation. Integrated RNA sequencing, RT-qPCR and molecular docking revealed that limopiperazine C exerts the anti-osteoclastogenic effect by modulating the ferroptosis signaling pathway via targeting heme oxygenase-1 (Hmox-1), positioning it as a promising lead compound for developing anti-osteoporotic agents.

Commentary: the TSP-1-CD47-integrin α4β1 axis—deciphering pathogenic mechanisms and therapeutic horizons in rheumatoid arthritis - Jie Guo; Feng-yi Mai; Xin-yu Li; Yu Liu; Jing-rong Liang; Xing-long Li; Chen-guang Li (Inflammation Research, 2026)

Hormonally and chemically induced male-to-female sex reversal is independent of Y-chromosome number in common carp - Kuangxin Chen; Yuanqi Guo; Yi Rong; Zhaoxian Li; Mouyan Jiang; Rui Li; Xiya Zhang; Yongming Li; Yulai Wei; Yanlong Song; Ji Chen; Binbin Tao; et al. (Aquaculture, 2026)

Mechanisms by Which Humic Acid Reduces Copper Toxicity in Citrus Roots Based on Omics and Physiology - Wei-Tao Huang; Rong-Rong Xie; Liang-Yuan Tong; Tian-Tian Xia; Jiuxin Guo; Ning-Wei Lai; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Plant Growth Regulation, 2026)

A room-temperature wireless NO2 gas sensor enabled by WO3 modified V2CTx nanosheets - Haineng Bai; Rui Guo; Yixin Zhou; Cheng Feng; Yiru Chen; Shengjie Zhang; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2026)

Nitrogen application regulates ecosystem multifunctionality through soil microbial diversity: a quantitative assessment - Tiantian Meng; Yanan Liu; Xiangqian Zhang; Jingjing Shi; Xiaoyu Zhao; Xuanyi Chen; Meiren Rong; Xingxing Guo; Shuli Wei; Jiawei Liu; Zhanyuan Lu (Plant and Soil, 2026)

Integrative bulk and single-cell transcriptomic analyses reveal nucleus pulposus cell fibrosis as a therapeutic target in intervertebral disc degeneration and identify quercetin as a potential antifibrotic agent - Peilin He; Jun Tao; Guo Li; Ye Mu; Rong Hu; Junming Chen; Wenqi Feng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Coordination-tailored conductive metal-organic frameworks boost CO2 electroreduction to ethylene for cascade ethylene glycol production - Hui Guo; Shao-Shuai Zhao; Duan-Hui Si; Weijin Li; Zi-Ao Chen; Rong Cao; Roland A. Fischer; Yuan-Biao Huang (Science Bulletin, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Hydrogeophysical Imaging and Joint Interpretation of Rainfall Infiltration on an Embanked Slope in the Mid-Lower Yangtze Hilly Region - Rong-wen Guo; Chen-yang Li; Zhuo Liu; Deng-kang Wang; Ming Yu (Applied Geophysics, 2026)

Automatic Detection of Disaster-Causing Organisms near the Waters of Nuclear Power Plant Based on LiveScope Scanning Sonar Images - Gangyi Yu; Shuo Wang; Wei Liu; Yongjian Xia; Yuchen Guo; Xiaolu Chen; Xueping Wei; Ao Chen; Zehua Lv; Chao Lu; Junbo Zhang; Rong Wan (Journal of Marine Science and Engineering, 2026)
Nuclear power serves as an efficient, clean, and low-carbon energy source that constitutes a significant component of the energy portfolio in numerous countries. Most nuclear power plants are predominantly situated in coastal regions, utilizing seawater as the ultimate heat sink for their cooling systems. Real-time monitoring of marine organism dynamics near water intakes is essential to mitigate the risk of unit shutdowns triggered by outbreaks of disaster-causing organisms (DCOs). This study employed LiveScope scanning sonar videos captured near the Ningde Nuclear Power Plant to develop a dataset for detecting the light spot area of the DCOs. We proposed a directionally optimized model, Bio-YOLO v7, which significantly enhances the detection of small targets in sonar images. The Bio-YOLO v7 model achieved precision, recall, and average precision rates of 85.29%, 83.28%, and 81.49%, respectively, demonstrating superior performance in identifying DCOs near the intakes of nuclear power plant. The light spot size of the DCOs exhibited significant periodic variations, serving as a crucial indicator for forecasting outbreak events.

Sulfur-doped TiO₂ with enhanced photocatalytic CO₂ reduction performance toward CO - Die He; Hui Ping Zhao; Hua Peng Guo; Rong Chen; Qiong Liu (Journal of Environmental Chemical Engineering, 2026)

Click chemistry-assisted hapten modification for enhanced immunoassay development: A promising strategy for clodinafop-propargyl detection in environmental and food samples - Yu Guo; Zhuanxu Xiang; Xinyue Ma; Rong Chen; Mei Dang; Xiaojun Jin; Anqi Chen; Ruyi Zeng; Lei Ke; Fanfan Yang (Food Chemistry, 2026)

Plant-soil feedback driven by root-associated fungal communities accelerates the secondary succession of bare saline-alkaline grassland patches - Xiaona Zheng; Yuhong Yin; Dan Yang; Jingjuan Bi; Wenlong He; Siya Li; Xiao Liang; Jigui Chen; Rong Wang; Zhiying Guo; Xing Li; Tao Zhang; et al. (Plant and Soil, 2026)

Genome-wide identification and expression analysis of the monosaccharide transporter (MST) gene family in response to exogenous sugar in wheat (Triticum aestivum L.) - Jun Zhang; Bo Zhang; Shuang Zhou; Wenzhong Tian; Rong Zhang; Yiren Chen; Binbin Guo; Chao Ma (Genetica, 2026)

Fatal infection of a novel canine/human reassortant H3N2 influenza A virus in the zoo-housed golden monkeys - Xia Wen; Rong Chen; Yingjun Lv; Jinzhu Geng; Jingjing Guo; Yaru Sun; Aohan Yang; Yuhao Dong; Meirong Li; Changlin Deng; Guodong Wang; Yongjie Liu (Veterinary Microbiology, 2026)

Magnesium deficiency limits electron transport efficiency and photosynthesis, and induces oxidative stress in tobacco - Rong-Rong Xie; Jingjuan Gao; Changzheng Wu; Jinping Guo; Qian Cheng; Hailu Wang; Tinmin Liang; Jianjun Lu; Chaoyuan Zheng; Liangquan Wu; Li-Song Chen; Songbiao Chen; et al. (Plant Science, 2026)

Performance stability and recovery strategy of pre-denitrification coupled partial nitritation/anammox-hydroxyapatite processes for enhanced organic matter, nitrogen and phosphorus removal from swine manure digestate - Yunzhi Qian; Shilong He; Fuqiang Chen; Junhao Shen; Chao Rong; Yan Guo; Yu Qin; Yu-You Li (Bioresource Technology, 2026)

Investigating the Therapeutic Efficacy of Quality-Controlled, miR-146a-5p-Enriched Small Extracellular Vesicles Derived From MSCs Against Idiopathic Pulmonary Fibrosis - Xin Wang; Lingjiao Meng; Qiuhong Wang; Ruixue Rong; Yu Zhang; Xiaohui Zhao; Chen Liang; Huizhen Guo; Li Deng; Zengqi Tan; Feng Guan; Yi Tan (Stem Cell Reviews and Reports, 2026)
Small extracellular vesicles derived from umbilical cord mesenchymal stem cells (UC-sEvs) may be used for the treatment of idiopathic pulmonary fibrosis (IPF) because of their ability to control inflammation and inhibit fibrosis. However, the lack of clarity regarding the treatment mechanism of IPF and the corresponding quality standards limit the clinical application of these small extracellular vesicles. Here, we established a good manufacturing practice (GMP) grade process for isolating UC-sEvs, and RNA-seq was performed to screen for potential therapeutic cargo in the product to confirm the therapeutic effect of nebulized UC-sEv agents against IPF. Functionally, UC-sEvs inhibited the pulmonary inflammatory response by regulating macrophage function, thereby suppressing the bleomycin toxicity-induced progression of fibrosis. Mechanistically, miR-146a-5p enrichment in UC-sEvs may be involved in alleviating bleomycin-induced IPF by targeting TRAF6/IRAK1 to negatively regulate inflammation. The proposed quality control strategy ensures the stability of the product across three batches, with RNA-seq analysis revealing highly similar miRNA expression profiles. The feasibility of using miR-146a-5p as a key therapeutic molecule has been validated. Finally, on the basis of the results of pharmacodynamics and key therapeutic molecule studies, we provided a detailed quality control standard for IPF therapy by nebulizing UC-sEv. These findings help understand how sEvs impact IPF and the possible consequences of their therapeutic usage and offer a quality standard reference. Graphical Abstract

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Oyster-mussel differences in cadmium accumulation linked to molecular weight distribution of Cd-binding proteins - Guangbin Zhong; Xue Cao; Sen Du; Canchuan Zhang; Li Zhang; Niklas Helle; Minwei Xie; Rong Chen; Qiao-Guo Tan (Journal of Hazardous Materials, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

An electrochemical reactor that enables continuous and uniform flow of high-viscosity slurry for semi-solid flow batteries - Chao Deng; Xiaoxin Li; Furong Xie; Miguel A. Modestino; Mustafa Kemal Bayazit; Barun Kumar Chakrabarti; Jeffrey Gostick; Zinan Wu; Rong Chen; Guo-Ming Weng (Chemical Engineering Journal, 2025)

Trio‐WES and functional validation reveals a novel splice site variant of SLC26A3 in a case with congenital chloride diarrhea and a systematic review of SLC26A3 mutations in China - Ruixue Zhang; Hongping Li; Rong Qiang; XinRu Gao; Jinzhen Guo; Guoqiang Chen; Qin Nan; Limei Zhong; Lin Wang (Molecular Genetics and Genomics, 2025)

Butein attenuates cardiac fibrosis by mediating TGF-β1/Smad signaling pathway after myocardial infarction - Mengmeng Deng; Rui Ma; Jinlei Li; Pan Lu; Rong Tan; Zhen Chen; Xin Guo (Journal of Molecular Histology, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

Sesquiterpenoids from Achillea setacea Waldst. & Kit. with anti-inflammatory activity by inhibiting the glycolytic pathway - Gui-Min Xue; Jin-Feng Xue; Jiang-Jing Duan; Hui-Ying Yang; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhi-Qiang Zhang; Rao Li; Dong-Rong Zhu; Guo-Sheng Li (Phytochemistry, 2025)

Wireless gas sensor based on monolayer Ti3C2Tx-modified GaN/CuO heterostructures for ultrafast and trace detection of NO2 gas - Haineng Bai; Cheng Feng; Rui Guo; Yiru Chen; Wenfeng Yuan; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2025)

Simulating the multiple effects of a diatom bloom on metal bioaccumulation in clams - Weiyi He; Fengjie Liu; Minwei Xie; Rong Chen; Qiao-Guo Tan (Marine Pollution Bulletin, 2025)

Decarbonization pathways and key emission drivers in ports: A scenario-based study of Shanghai Port - Rong Shi; Yue Chen; Shuxia Yang; Xiaopeng Guo; Xiongfei Wang (Sustainable Cities and Society, 2025)

Tracing toxic pollutants in coastal urban atmosphere: A case study on the particle-size distribution, sources, and health risks of PCDD/Fs, PCBs, PAHs, and substituted PAHs - Zhangpeng Guo; Shuai Sun; Rong Cao; Nan Jiang; Naibing Liang; Zichen Wang; Jiasen Guo; Minzhen Li; Xing Liu; Ningbo Geng; Jiping Chen (Journal of Hazardous Materials, 2025)

Refining marine metal biomonitoring through insights into allometry in green mussels - Yuqing Liao; Haiyan Xiong; Wenze Xiao; Jun Liu; Minwei Xie; Rong Chen; Qiao-Guo Tan (Environmental Pollution, 2025)

Impact of Ca supplement to the single-stage partial nitritation/anammox-hydroxyapatite process in treating swine manure digestate: deterioration mechanism and recovery strategy - Yunzhi Qian; Shilong He; Chao Rong; Yan Guo; Fuqiang Chen; Junhao Shen; Yu Qin; Yu-You Li (Chemical Engineering Journal, 2025)

Residual polyacrylamide-induced membrane fouling in short-flow coagulation-ultrafiltration: Behavior and mechanism - Mohan Wei; Yaozhong Zhang; Xing Zheng; Chi Zhang; Jiheng Duan; Kai Guo; Menghan Wang; Dongfei Li; Tianshuo Huang; Rong Chen (Chemical Engineering Journal, 2025)

Effects of aged microplastics on the abundance of antibiotic resistance genes in oysters and their excreta - Yifang Yu; Jing Qian; Weichao Wang; Minwei Xie; Qiao-Guo Tan; Rong Chen (Marine Environmental Research, 2025)

Why is the combined treatment of copper and aluminum more toxic to citrus than single factor treatment? - Wen-Shu Chen; Ti Wu; Tian-Tian Xia; Liang-Yuan Tong; Fei Lu; Xin Ye; Jiuxin Guo; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2025)

In Situ isotope tracing for metal bioaccumulation in open waters: Implications for interpreting biomonitoring data and safe seafood aquaculture - Haiyan Xiong; Tao Wang; Xue Cao; Jing Qian; Stuart L. Simpson; Rong Chen; Qiao-Guo Tan; Minwei Xie (Journal of Hazardous Materials, 2025)

The evolutionary history of the Methyltransf_FA domain and its role in JH signal in silkworm, Bombyx mori - Chunyang Wang; Yang Yu; Qi Shen; Rong Xiong; Meiwei Guo; Jiamei Zhao; Dongsheng Yan; Rongcheng Zhang; Ping Chen (Insect Biochemistry and Molecular Biology, 2025)

Cambrian mid-ocean ridge basalt-like mafic rocks and associated boninites in the Dachadaban ophiolite from the North Qilian Block, northwest China: Petrogenesis and implications for back-arc extension - De-Chao Li; Xi-Jun Liu; Xiao Liu; Gang Chen; Qi Song; Hao Tian; Zheng-Lin Li; Peng-De Liu; Rong-Guo Hu (Geochemistry, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

An energy-saving pH-asymmetric electrolyzer for simultaneous methane conversion and hydrogen production - Rong Chen; Furong Xie; Zinan Wu; Xiaoxin Li; Chao Deng; Zhenpeng Yao; Guo-Ming Weng (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Low Nitrogen with Split Application Strategy Enhances Antioxidative Defense, Photosynthesis, and Enzymatic Activities to Waxy Maize Under Heat Stress - Song Xu-dong; Ahmad Irshad; Zhang Hui-min; Zhang Zhen-liang; Zhou Guang-fei; Chen Guo-qing; Mao Yu-xiang; Lu Hu-hua; Hao De-rong (Journal of Plant Growth Regulation, 2025)

Dose-response pattern of marine macroalgae Gracilariopsis heteroclada to three fluoroquinolones and the cause-effect relationship of dose, growth, toxicity and sorption - Kun Lin; Youyou Guo; Rong Xin; Enyi Xie; Xuefeng Wang; Jianjun Cui; Jinhui Wu; Zhaowei Huang; Yong Liu; Shaoliang Lyu; Sipan Wang; Yongjian Huang; et al. (Algal Research, 2025)

Direct recovery of high-purity uranium from fluoride-containing nuclear wastewater via extraction materials with ensemble Lewis sites and a tandem electrochemical device - Guo Li; Yan Liu; Chi Jiao; Zhengyu Jiang; Juan Zhang; Tao Chen; Tao Lin; Rong He; Wenkun Zhu; Xiangke Wang (Water Research, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Neuroprotective lindenane sesquiterpenoids from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Shan-Rong Luo; Qian-Qing Liu; Rui-Si Tang; Ning-Yu Chen; Di Luo; Lu Guo; Jia Li; Rui Wu; Zha-Jun Zhan (Phytochemistry, 2025)

Hydrodynamic perturbations on contaminant behavior in low-permeability sediments: porewater metal dynamics and risk assessment implications - Ning Wang; Hongwei Hu; Wenze Xiao; Qiao-Guo Tan; Rong Chen; Minwei Xie; Stuart L. Simpson (Environmental Pollution, 2025)

Machine learning-driven molecular generation for accelerated screening of high-performance flame retardants in epoxy resin composites - Zhongwei Chen; Chunlei He; Kai Wang; Feng Rong; Long Xiang; Ziwei Zuo; Changliang Wang; Xinyuan Yang; Yong Guo; Juncheng Jiang; Yuan Yu (Chemical Engineering Journal, 2025)

Corrigendum to “Stable isotope tracing reveals glucose metabolism characteristics of drug-resistant B-cell acute lymphoblastic leukemia” [Analytica Chimica Acta 1352 (2025) 343884] - Rong Hu; Zhengwei Duan; Mengyao Wang; Mengting Liu; Yaoxin Zhang; Yanxi Lu; Yuhan Qian; Enjie Wei; Jianghua Feng; Pengfei Guo; Yang Chen (Analytica Chimica Acta, 2025)

Active spermatogenesis in YY supermale common carp makes it suitable for potential control of this invasive species - Kuangxin Chen; Yi Rong; Yuanqi Guo; Mouyan Jiang; Yulai Wei; Xishuang Shan; Yongming Li; Yanlong Song; Ji Chen; Binbin Tao; Wei Hu (Aquaculture, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Effect of high in-situ asymmetric stress on the brittle failure of the boundary of an underground powerhouse - Ben-Guo He; Shi-Chen Qiu; Xia-Ting Feng; En-Rong Liu; Tao Chen; Shencun Yan (Bulletin of Engineering Geology and the Environment, 2025)

Plasmon-enhanced fluorescence sensor based on Au nanocages for sensitive detection of norepinephrine - Chenye Xu; Shilin Chen; Wen Sun; Rong Xu; Xiangyuan Yin; Dongsheng Guo; Yaqiong Yang (Analytica Chimica Acta, 2025)

Oil pollution risks on coastlines in the Eastern China Seas - Ruichen Cao; Junting Guo; Zengrui Rong; Haibo Chen; Xianqing Lv (Environmental Pollution, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Stable isotope tracing reveals glucose metabolism characteristics of drug-resistant B-cell acute lymphoblastic leukemia - Rong Hu; Zhengwei Duan; Mengyao Wang; Mengting Liu; Yaoxin Zhang; Yanxi Lu; Yuhan Qian; Enjie Wei; Jianghua Feng; Pengfei Guo; Yang Chen (Analytica Chimica Acta, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Development of a multiplex PCR assay for detection of Riemerella anatipestifer serotype 1 and serotype 2 strains - Mengsi Wu; Rong Guo; Meitong Chen; Min Zhu; Zongchao Chen; Chan Ding; Shengqing Yu (Veterinary Microbiology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Petrogenesis and age of granitoids associated with the Dongshan Cu polymetallic deposit, East Kunlun Orogenic Belt, NW China: Implications for the Middle to Late Triassic tectonic setting and Cu polymetallic mineralization - Yi-Chen Chen; Zheng-Jiang Ding; Jun-Wei Bo; Shi-Jiong Han; Ting-Ting Li; Pan Ji; Rong-Qiang Guo (Geochemistry, 2025)

Synergetic “amine scissors” break down cured epoxy resins with nearly 100% degradation efficiency - Furong Xie; Rong Chen; Chao Deng; Xiaoxin Li; Huiyan Yang; Yu Xie; Song Wang; Guo-Ming Weng (Chemical Engineering Journal, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Deciphering the antibiotic resistome in stratified source water reservoirs in China: Distribution, risk, and ecological drive - Honghong Guo; Rong Li; Yuhang Su; Shuhong Xue; Na Li; Fan Chen; Xuanzi Zhangsun; Haihan Zhang; Xiaoyan Liu; Tinglin Huang (Journal of Hazardous Materials, 2025)

Hidden threat in turbid waters: Quantifying and modeling the bioaccumulation and risks of particulate metals to clams - Jing Qian; Xue Cao; Haiyan Xiong; Fengjie Liu; Minwei Xie; Rong Chen; Qiao-Guo Tan (Environmental Pollution, 2025)

Drivers and spatial distribution of soil organic carbon and total nitrogen in China’s drylands - Shihang Zhang; Yusen Chen; Bo Zhu; Yongxing Lu; Hao Guo; Xing Guo; Ye Tao; Jing Zhang; Xiaoying Rong; Benfeng Yin; Yongxin Zang; Xiaobing Zhou; et al. (CATENA, 2025)

Comammox and ammonia-oxidizing archaea dominated the nitrification under different nitrogen fertilizer levels in acid purple soil of Southwest China - Jun Xie; Jianguo Jiang; Jie Lu; Wencai Dai; Huarong Guo; Yuanxue Chen; Rong Huang; Zifang Wang; Ming Gao (Applied Soil Ecology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Transformation and environmental fate of 6-OH-BDE-47 and 6-MeO-BDE-47 in oxic and anoxic sediments - Yunfeng Ma; Meilin Chen; Pan Yi; Ruixin Guo; Rong Ji; Jianqiu Chen; Yanhua Liu (Journal of Hazardous Materials, 2025)

Draft Genome of Naganishia uzbekistanensis from a Clinical Pulmonary Infection - Rong-Chen Dai; Xin-Fei Chen; Xin Fan; Li Gu; Li Zhang; Dan Guo; Ying-Chun Xu; Meng Xiao (Mycopathologia, 2025)

Enriching bottom acceptors for high-performance inkjet-printed organic solar cells - Xingze Chen; Lifeng Sang; Yuanyuan Jiang; Yiyu Chen; Qing Zhang; Rong Huang; Fengqi Guo; Guanghao Lu; Xiaozhang Zhu; Qi Chen; Chang-Qi Ma; Qun Luo (Chemical Engineering Journal, 2025)

Off-site production of plasma-activated water for efficient disinfection: The crucial role of high valence NOx and new chemical pathways - Zifeng Wang; Xiangyu Wang; Shenghang Xu; Renwu Zhou; Mingyan Zhang; Wanchun Li; Zizhu Zhang; Luge Wang; Jinkun Chen; Jishen Zhang; Li Guo; Dandan Pei; et al. (Water Research, 2024)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

Occurrence and fate of atmospheric short/medium chain chlorinated paraffins: Size distribution and inhalation exposure - Naibing Liang; Rong Cao; Nan Jiang; Chengcheng Shi; Zhangpeng Guo; Yuan Gao; Ruiqin Zhang; Haijun Zhang; Jiping Chen; Ningbo Geng (Science of The Total Environment, 2024)

Microscopic mechanisms and durability evaluation under freeze-thaw conditions of heavy metal solidification in red mud-slag geopolymer - Lu Zhou; Xin Xu; Qing Wang; Junboum Park; Yongming Han; Lisheng Guo; Rong Chen (Journal of Environmental Chemical Engineering, 2024)

Towards advanced removal of organics in persulfate solution by heterogeneous iron-based catalyst: A review - Baihui Cui; Tingting Tian; Luchun Duan; Hongwei Rong; Zhihua Chen; Shiyi Luo; Dabin Guo; Ravi Naidu (Journal of Environmental Sciences, 2024)

MOF for encapsulating ionic liquids serves as an electrocatalyst to decrease the ignition delay time of electrically controlled solid propellants - Baiquan Chen; Cailing Zhang; Zhenguo Pang; Xugang Rong; Yanli Guo; Wei He (Chemical Engineering Journal, 2024)

An extension to ensemble forecast of conditional nonlinear optimal perturbation considering nonlinear interaction between initial and model parametric uncertainties - Bin Mu; Zi-Jun Zhao; Shi-Jin Yuan; Xing-Rong Chen; Bo Qin; Guo-Kun Dai (Atmospheric Research, 2024)

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Novel targets and their functions in the prognosis of uterine corpus endometrial cancer patients - Xin Sui; Penghui Feng; Jie Guo; Xingtong Chen; Rong Chen; Yanmin Zhang; Falin He; Feng Deng (Journal of Applied Genetics, 2024)

Neutralizing chimeric heavy-chain antibody targeting the L-HN domain of Clostridium botulinum neurotoxin type F - Kaiyue Sun; Shudi Luo; Yujia Jiang; Jiazheng Guo; Xi Wang; Kexuan Cheng; Changyan Xu; Yixiao Zhang; Chen Gao; Jiansheng Lu; Peng Du; Yunzhou Yu; et al. (Archives of Toxicology, 2024)

FGTN: Fragment-based graph transformer network for predicting reproductive toxicity - Jia-Nan Ren; Qiang Chen; Hong-Yu-Xiang Ye; Cheng Cao; Ya-Min Guo; Jin-Rong Yang; Hao Wang; Muhammad Zafar Irshad Khan; Jian-Zhong Chen (Archives of Toxicology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Silver nanoparticles regulate antibiotic resistance genes by shifting bacterial community and generating anti-silver genes in estuarine biofilms - Xing-pan Guo; Xin-jie Chen; Nazupar Sidikjan; Rong-rong Sha (Aquatic Toxicology, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Gum arabic coating alleviates chilling injury of cold-stored peach by regulating reactive oxygen species, phenolic, and sugar metabolism - Zengyu Gan; Yupei Zhang; Ziteng Jin; Yongjie Wang; Jiali Li; Caining Yang; Qing Cao; Jinyin Chen; Zhenbang Rong; Xuming Lu; Suqin Guo (Food Chemistry, 2024)

Identification of peptides from Corneum Galli Gigeri Endothelium and inhibiting H2O2-induced gastric mucosa associated with the Rho signaling pathway - Rong xiang Guo; Huiying Zhang; Yao Chen; Pan Li; Bing Du (Food Bioscience, 2024)

N, S-carbon quantum dots as inhibitor in pickling process of heat exchangers for enhanced performance in multi-stage flash seawater desalination - Bochuan Tan; Yan Liu; Haiqin Ren; Zhili Gong; Xin Li; Wenpo Li; Lei Guo; Rong Chen; Juxiang Wei; Qingwei Dai; Abeer A. AlObaid (Desalination, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

BaP/BPDE exposure causes human trophoblast cell dysfunctions and induces miscarriage by up-regulating lnc-HZ06-regulated IL1B - Jiarong Guo; Jingsong Zhao; Peng Tian; Zhongyan Xu; Rong Wang; Weina Chen; Xiaoqing Wang; Shukun Wan; Yang Yang; Huidong Zhang (Journal of Hazardous Materials, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

FOXP4-AS1 promotes CD8+ T cell exhaustion and esophageal cancer immune escape through USP10-stabilized PD-L1 - Guo-yi Shen; Yi Zhang; Rong-zhi Huang; Zhi-yong Huang; Le-yi Yang; Ding-zhu Chen; Shao-bin Yang (Immunologic Research, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Assessment of Heavy Metal Pb2+ Adsorption and Migration in Sand with Varied Particle Gradations: Implications for Environmental Control and Remediation Strategies - Lu Zhou; Xin Xu; Rong Chen; Yongming Han; Dongxue Hao; Lisheng Guo (Water, Air, & Soil Pollution, 2024)

Industrial hemp (Cannabis sativa L.) can utilize and remediate soil strongly contaminated with Cu, As, Cd, and Pb by phytoattenuation - Yuan Guo; Lan Wen; Xinlin Zhao; Chen Xing; Rong Huang (Chemosphere, 2024)

Sulfur migration mechanism of pig manure in supercritical water: A combined experimental and DFT study - Shuyuan Zhang; Mingming Du; Hui Ge; Siqi Rong; Yunan Chen; Liejin Guo (Journal of Hazardous Materials, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Effects of arsenic on the transport and attachment of microplastics in porous media - Jia Guo; Haifeng Rong; Lei He; Cuibai Chen; Baogang Zhang; Meiping Tong (Journal of Hazardous Materials, 2024)

Effects of dietary supplementation with green lentil (Lens culinaris) hulls on NAFLD: Focus on intestinal and hepatic metabolism - Fanghua Guo; Dongying Chen; Rong Tsao; Fereidoon Shahidi; Hua Xiong; Hua Zhang; Li Jiang; Yong Sun (Food Bioscience, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Experimental Investigation of Desiccation Cracking of Jilin Ball Clay Under Wet–Dry Cycles - Yucong Gao; Dongxue Hao; Yiming Zhu; Rong Chen; Xuejun Liu; Ruifeng Guo (Geotechnical and Geological Engineering, 2024)

Study on spray characteristics of micro-nano bubble premixed fuel - Rong Xuan; Liang Guo; Ningning Cai; Wanchen Sun; Yuying Yan; Hao Zhang; Yanling Chen; Han Wang; Junfeng Zhang; Youxin Ge (Fuel, 2024)

Contact-electro-catalysis for degradation of trace antibiotics in wastewater - Da-Qi Cao; Rong-Kun Fang; Yi-Xuan Song; Ming-Guo Ma; Haiyan Li; Xiao-Di Hao; Rongling Wu; Xiangyu Chen (Chemical Engineering Journal, 2024)

Ent-atisane diterpenoids from Euphorbia wallichii and their anti-influenza A virus activity - Jie Zhang; Xiao-Jia Guo; Xiao-Juan Chen; Rong-Rong Zhang; Bai-Ping Ma; Zhong-Qiu Liu (Phytochemistry, 2024)

A new cleistanthane diterpenoid from the cultures of a mutant of Calcarisporium arbuscula NRRL 3705 - Hui Lu; Hong-Yu Chen; Shan-Rong Luo; Lu Guo; Di Luo; Lie-Feng Ma; Zha-Jun Zhan (Phytochemistry Letters, 2024)

Boron-mediated amelioration of copper toxicity in Citrus sinensis seedlings involved reduced concentrations of copper in leaves and roots and their cell walls rather than increased copper fractions in their cell walls - Huan-Huan Chen; Zhi-Chao Zheng; Dan Hua; Xu-Feng Chen; Zeng-Rong Huang; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

Synergistic effect of the framework boron and Al-rich region to enhance the metal-support interaction for boosting Pd-based catalyst activity of dimethyl carbonate synthesis - Siqi Wu; Jianshan Chen; Rong Guo; Haoyi Tong; Shanshan Zong; Zhifang Diao; Yeyan Qin; Yuangen Yao (Chemical Engineering Journal, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Comprehensive plasmid toolkit for multipart assembly in the Dunaliella salina nuclear system - Hao-Hong Chen; Yu-Chen Xie; Shan-rong Xie; Jian-Guo Jiang (Algal Research, 2024)

Potential Role of Bmal1 in Lipopolysaccharide-Induced Depression-Like Behavior and its Associated "Inflammatory Storm" - Dan-Dan Xu; Zhi-Qi Hou; Ya-Yun Xu; Jun Liang; Ye-Jun Gao; Chen Zhang; Fan Guo; Dan-Dan Huang; Jin-Fang Ge; Qing-Rong Xia (Journal of Neuroimmune Pharmacology, 2024)

Epidural administration of large dose of opioid μ receptor agonist may impair cardiac functions and myocardial viability via desensitizing transient receptor potential vanilloid 1 - Xiang Ma; Zheng Guo; Mu-Rong Li; Lu Chen; Xing Zhao; Tian-Qi Wang; Tao Sun (Toxicology and Applied Pharmacology, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Molecular dynamics simulation and experimental analysis of nucleation and growth mechanism of mixed inorganic salts in supercritical water - Siqi Rong; Ruoyu Wang; Anlan Xie; Zhiyong Peng; Peng Cao; Mingyi Zhang; Jinhua Cui; Yunan Chen; Liejin Guo (Chemical Engineering Journal, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Fabrication of compact zein-chondroitin sulfate nanocomplex by anti-solvent co-precipitation: Prevent degradation and regulate release of curcumin - Yufan Shi; Shuang Rong; Tingxian Guo; Ruyi Zhang; Duoxia Xu; Yahong Han; Fuguo Liu; Jiaqi Su; Hongxin Xu; Shuai Chen (Food Chemistry, 2024)

Microbial stratification protects denitrifying anaerobic methane oxidation archaea and bacteria from external oxygen shock in membrane biofilm reactor - Pan-Long Lv; Chuan Jia; Xu Guo; He-Ping Zhao; Rong Chen (Bioresource Technology, 2024)

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Osthole protects H9c2 cardiomyocytes against trastuzumab-induced damage by enhancing autophagy through the p38MAPK/mTOR signaling pathway - Huan Hou; Yaping Yang; Rong Chen; Zhiping Guo (Toxicology in Vitro, 2023)

Carbon quantum dot-induced developmental toxicity in Daphnia magna involves disturbance of symbiotic microorganisms - Yunfeng Ma; Yanhua Liu; Wenling Chen; Fei Li; Ruixin Guo; Rong Ji; Jianqiu Chen (Science of The Total Environment, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Developmental toxicity in Daphnia magna induced by environmentally relevant concentrations of carbon black: From the perspective of metabolomics and symbiotic bacteria composition - Yunfeng Ma; Ruixin Guo; Zixuan Zheng; Peng Min; Rong Ji; Jianqiu Chen; Yanhua Liu (Chemosphere, 2023)

Enhancing simultaneous desulfurization and denitrification efficiency of cement kiln exhaust gas via co-catalytic Fenton oxidation process - Tongsheng Zhang; Hui Peng; Rong Chen; Yiqun Guo; Jiawei Wang; Xinzhi Chen; Jiangxiong Wei; Qijun Yu (Journal of Cleaner Production, 2023)

Species diversity and related ecology of chiggers on small mammals in a unique geographical area of Yunnan Province, southwest China - Yu Guo; Juan-Xiu Zhou; Xian-Guo Guo; Wen-Yu Song; Cheng-Fu Zhao; Zhi-Wei Zhang; Rong Fan; Ting Chen; Yan Lv; Peng-Wu Yin; Dao-Chao Jin (Experimental and Applied Acarology, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Inactivation of airborne pathogenic microorganisms by plasma-activated nebulized mist - Li Guo; Pengyu Zhao; Yikang Jia; Zifeng Wang; Min Chen; Hao Zhang; Dingxin Liu; Yong Zhang; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2023)

Icariin inhibits hypertrophy by regulation of GPER1 and CaMKII/HDAC4/MEF2C signaling crosstalk in ovariectomized mice - Wenxia Zhao; Xiaoli Shan; Xueqin Li; Shuang Lu; Lei Xia; Huihua Chen; Chen Zhang; Wei Guo; Ming Xu; Rong Lu; Pei Zhao (Chemico-Biological Interactions, 2023)

Coupling and coordinated development of low-carbon economy and green finance: an empirical study of the Yangtze River Delta region in China - Shujie Sun; Peixiu Chen; Zehui Guo; Ling Miao; Rong Zhu; Xuepeng Qian; Weisheng Zhou (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Interspecies calibration for biomonitoring metal contamination in coastal waters using oysters and mussels - Xue Cao; Guangbin Zhong; Ke Pan; Jing Qian; Minwei Xie; Rong Chen; Yongyan Liao; Qiao-Guo Tan (Science of The Total Environment, 2023)

Heavy metal(loid)s in agriculture soils, rice, and wheat across China: Status assessment and spatiotemporal analysis - Cheng-Chen Wang; Qiao-Chu Zhang; Chang-An Yan; Guo-Yong Tang; Meng-Yan Zhang; Lena Q. Ma; Rong-Hui Gu; Ping Xiang (Science of The Total Environment, 2023)

Corrigendum to “Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels” [Food Hydrocolloids 139 (2023) 108527] - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Spatiotemporal characteristics of extreme hydrometeorological events and its potential influencing factors in the Huaihe River Basin, China - Rong Gan; Dandan Li; Changzheng Chen; Feng Yang; Xinyu Zhang; Xiaomin Guo (Stochastic Environmental Research and Risk Assessment, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Rational design of Ga-substituted NaY zeolites with controllable acidity for remarkable carbonylation of methyl nitrite to dimethyl carbonate - Siqi Wu; Rong Guo; Jianshan Chen; Runping Ye; Yeyan Qin; Hanying Wu; Shanshan Zong; Yang Liu; Yuangen Yao (Fuel, 2023)

Engineering single-atom catalysts as multifunctional polysulfide and lithium regulators toward kinetically accelerated and durable lithium-sulfur batteries - Donghua Wang; Kaikai Ma; Jiamao Hao; Wenyuan Zhang; Haofeng Shi; Chengdeng Wang; Zhihao Xiong; Zhiming Bai; Fu-Rong Chen; Junjie Guo; Bingshe Xu; Xiaoqin Yan; et al. (Chemical Engineering Journal, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Phytoplankton community changes in a coastal upwelling system during the last century - Peng Peng; Rong Bi; Julian P. Sachs; Jie Shi; Yifei Luo; Weifang Chen; Chih-An Huh; Meng Yu; Yali Cao; Yaoyao Wang; Zhong Cao; Xiaohan Bao; et al. (Global and Planetary Change, 2023)

Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Di-(2-ethylhexyl) phthalate impairs angiogenesis and hematopoiesis via suppressing VEGF signaling in zebrafish - Yang-Xi Hu; Bo-Wen Hu; Ya-Sha Chen; Hong-Min You; Mei-Rong Bai; Lu-Jun Zhang; Zhi-Fu Guo; Chun Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Orange protein (DbOR) from the salt-tolerant green alga Dunaliella bardawil mediates photosynthesis against heat stress via interacting with DbPsbP1 - Ming-Hua Liang; Jv-Liang Dai; Shan-Rong Xie; Jing-Xuan Wu; Hao-Hong Chen; Jian-Guo Jiang (Algal Research, 2023)

Visible-light-driven photocatalytic degradation of tetracycline hydrochloride by Z-scheme Ag3PO4/1T@2H-MoS2 heterojunction: Degradation mechanism, toxicity assessment, and potential applications - Xiuyi Hua; Haijun Chen; Chang Rong; Francis Addison; Deming Dong; Jiao Qu; Dapeng Liang; Zhiyong Guo; Na Zheng; Haiyang Liu (Journal of Hazardous Materials, 2023)

Astaxanthin, bile acid and chlorogenic acid attenuated the negative effects of high-fat diet on the growth, lipid deposition, and liver health of Oncorhynchus mykiss - Wei Zhao; Rong Yao; Han-Lin Wei; Yu-Cai Guo; An-Qi Chen; Bao-Yang Chen; Jin-Niu (Aquaculture, 2023)

The phosphorus harvest from low-temperature mainstream wastewater through iron phosphate crystallization in a pilot-scale partial nitritation/anammox reactor - Yan Guo; Eli Hendrik Sanjaya; Tianjie Wang; Chao Rong; Zibin Luo; Yi Xue; Hong Chen; Yu-You Li (Science of The Total Environment, 2023)

Synergistic and antagonistic effects of preharvest salicylic acid and postharvest 1-methylcyclopropene treatments on the storage quality of apricot - Changchang Liang; Xinzhi Cui; Chanchan Sun; Sunxiang Ye; Ningxin Huang; Rong Chen; Aidi Zhang; Yanqing Yang; Hansheng Gong; Shuyang Sun; Fengjun Guo; Xinguang Fan; et al. (Food Chemistry, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Adaptation of anammox consortia in microbial fuel cell to low temperature: Microbial community and predictive functional profiling - Geer An; Rong Yan; Zhimin Fu; Zepeng Chen; Yaru Guo; Jun Yang; Yongheng Zhou (Bioresource Technology, 2023)

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

Personalizing atomoxetine dosing in children with ADHD: what can we learn from current supporting evidence - Di Fu; Hong-Li Guo; Ya-Hui Hu; Wei-Rong Fang; Qian-Qi Liu; Jing Xu; Dan-Dan Wu; Feng Chen (European Journal of Clinical Pharmacology, 2023)

Combined effect of Cu- and ZnO- NPs on antibiotic resistance genes in an estuarine water - Yu-ru Chen; Rong-rong Sha; Xiao-li Sun; Xing-pan Guo; Yi Yang (Frontiers in Marine Science, 2023)
Most studies of whether and how nanoparticles (NPs) affect antibiotic resistance genes (ARGs) focus on testing single NPs type. In this study, we determined the combined effect of Cu- and ZnO- NPs in the water samples collected from the Yangtze River Estuary and found the effect differs greatly from that produced by individual NPs. The results showed that the Cu- and ZnO- NPs co-exposure resulted in an enrichment of ARGs, whereas individual Cu- and ZnO- NPs exposure decreased the abundance of ARGs. Furthermore, the co-exposure of Cu- and ZnO- NPs induced obvious changes in the microbial communities compared to the control communities. Redundancy analysis suggested that the microbial community contributed the most (43.5%) to the ARG profiles, followed by dissolved metal ions (25.7%), MRGs, (19.4%), and MGEs (4.4%). Network analysis found several potential hosts (such as Mycobacterium and Escherichia coli ) and implied the extent of the risk of ARG transmission into various environmental niches by these common microbes.

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

Poly(ionic liquid) boosts overall performance of electrocatalytic reduction of low concentration of CO gas - Guo-Yi Duan; Xiao-Qiang Li; Jun-Wu Chen; Guang-Rong Ding; Peng-Xin Guan; Bao-Hua Xu (Chemical Engineering Journal, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Study on the Relationship Between Diet, Physical Health and Gut Microflora of Chinese College Students - Xiafen Hu; Jiaqi Guo; Jiadun Wang; Wanxin Liu; Xiaochen Xiang; Siyang Chen; Xinquan Li; Jinhan Tang; Wei Zhang; Hui Chen; Rong Shu; Qingming Wu; et al. (Current Microbiology, 2022)

Establishment of a novel myocarditis mouse model based on cyclosporine A - Tian Hao Zhao; Yi Xuan Jiang; Kai Qin Chen; Dan Qiu; Yan Zhe Xu; Chun Ye; Ting Ren; Bo Zhang; Bin Dai; Jue Hu; Jun Lu; Fang Liang Zhou; et al. (Genes & Genomics, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Selenium Deficiency Induces Autophagy in Chicken Bursa of Fabricius Through ChTLR4/MyD88/NF-κB Pathway - Ruili Zhang; Qing Liu; Rong Guo; Di Zhang; Yang Chen; Guangxing Li; Xiaodan Huang (Biological Trace Element Research, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Monascuslactams A–D, cytotoxic γ-lactams from marine fungus Monascus albidus BB3 - Qi Guo; Xiao-Ming Dai; Wen-Jian Lan; Liu-Ping Chen; Chi-Keung Lam; Gong-Kan Feng; Rong Deng; Xiao-Feng Zhu; Hou-Jin Li (Natural Product Research, 2022)

Monitoring the behavior of subway tunnels during early operation in saturated soft strata - Ben-Guo He; Rong-Li Zhen; Tian-Yu Chen; Hong-Pu Li (Bulletin of Engineering Geology and the Environment, 2022)

Bioactive isocoumarins isolated from a mangrove-derived fungus Penicillium sp. MGP11 - Rong-Qing Mei; Bin Wang; Wei-Nv Zeng; Guo-Lei Huang; Guang-Ying Chen; Cai-Juan Zheng (Natural Product Research, 2022)

Selenium Deficiency Causes Inflammatory Injury in the Bursa of Fabricius of Broiler Chickens by Activating the Toll-like Receptor Signaling Pathway - Yu Bai; Ruili Zhang; Qing Liu; Rong Guo; Guangxing Li; Bin Sun; Di Zhang; Yang Chen; Xiaodan Huang (Biological Trace Element Research, 2022)

Effect of Triaxial Loading and Unloading on Crack Propagation and Damage Behaviors of Sandstone: An Experimental Study - Yan Chen; Wenbing Guo; Jianping Zuo; Shuai Heng; Rong Dou (Rock Mechanics and Rock Engineering, 2021)

Yak Excreta Application Alter Nitrification by Regulating the Ammonia-Oxidizing Bacterial Communities in Wetland Soils - Li Chen; Rong Bo Zheng; Jun Qin Gao; Ming Hua Song; Xue Lian Guo (Journal of Soil Science and Plant Nutrition, 2021)

Effects of Gap Resonance on the Hydrodynamics and Dynamics of a Multi-Module Floating System with Narrow Gaps - Mingsheng Chen; Hongrui Guo; Rong Wang; Ran Tao; Ning Cheng (Journal of Marine Science and Engineering, 2021)
Multi-module floating system has attracted much attention in recent years as ocean space utilization becomes more demanding. This type of structural system has potential applications in the design and construction of floating piers, floating airports and Mobile Offshore Bases (MOBs) generally consists of multiple modules with narrow gaps in which hydrodynamic interactions play a non-neglected role. This study considers a numerical model consisting of several rectangular modules to study the hydrodynamics and dynamics of the multi-module floating system subjected to the waves. Based on ANSYS-AQWA, both frequency-domain and time-domain simulations are performed to analyze the complex multi-body hydrodynamic interactions by introducing artificial damping on the gap surfaces. Parametric studies are carried out to investigate the effects of the gap width, shielding effects of the multi-body system, artificial damping ratio on the gap surface, and the dependency of the hydrodynamic interaction effect on wave headings is clarified. Based on the results, it is found that the numerical analysis based on the potential flow theory with artificial damping introduced can produce accurate results for the normal wave period range. In addition, the effects of artificial damping on the dynamics and connector loads are investigated by using a simplified RMFC model. For the case of adding an artificial damping ratio of 0.2, the relative heave and pitch motions are found to be reduced by 33% and 50%, respectively. In addition, the maximum cable and fender forces are found to be reduced by 50%, compared with the case without viscosity correction.

One new α , β -unsaturated 7-ketone sterol from the mangrove-derived fungus Phomopsis sp.MGF222 - Xiao-Chen Zhu; Guo-Lei Huang; Rong-Qing Mei; Bin Wang; Xue-Ping Sun; You-Ping Luo; Jing Xu; Cai-Juan Zheng (Natural Product Research, 2021)

A new phenol derivative isolated from mangrove-derived fungus Eupenicillium sp. HJ002 - Rong-Qing Mei; Xu-Hua Nong; Bin Wang; Xue-Ping Sun; Guo-Lei Huang; You-Ping Luo; Cai-Juan Zheng; Guang-Ying Chen (Natural Product Research, 2021)

Mortality risk attributable to diurnal temperature range: a multicity study in Yunnan of southwest China - Yujin Wang; Yang Chen; Jiaqi Chen; Rong Wu; Pi Guo; Shun Zha; Qingying Zhang (Environmental Science and Pollution Research, 2021)

Genotypic variation in nitrogen utilization efficiency in oilseed rape is related to the coordination of leaf senescence and root N uptake during reproductive stage - Huiying He; Yuyu Xie; Anyu Zhao; Wencong Hu; Xiao Guo; Anthony J. Miller; Xiaoming Wu; Biyun Chen; Rong Zhang; Hui Tian; Yajun Gao (Plant and Soil, 2021)

MiR-150-5p regulate T cell activation in severe aplastic anemia by targeting Bach2 - Yingmei Li; Jifeng Yu; Fang Wang; Rong Guo; Haizhou Xing; Yali Chen; Dandan Chen; Xinsheng Xie; Dingming Wan; Zhongxing Jiang (Cell and Tissue Research, 2021)

Variation in rare earth element (REE), aluminium (Al) and silicon (Si) accumulation among populations of the hyperaccumulator Dicranopteris linearis in southern China - Wen-Shen Liu; Hong-Xiang Zheng; Chang Liu; Mei-Na Guo; Shi-Chen Zhu; Yue Cao; Rong-Liang Qiu; Jean Louis Morel; Antony van der Ent; Ye-Tao Tang (Plant and Soil, 2021)

Involvement of Mitophagy in Aluminum Oxide Nanoparticle–Induced Impairment of Learning and Memory in Mice - Tao Huang; Weiwei Guo; Yanhong Wang; Lijun Chang; Nan Shang; Jin Chen; Rong Fan; Lan Zhang; Xiaocheng Gao; Qiao Niu; Qinli Zhang (Neurotoxicity Research, 2021)

Carbon monoxide-triggered health effects: the important role of the inflammasome and its possible crosstalk with autophagy and exosomes - Rong-Jane Chen; Yu-Hsuan Lee; Tzu-Hao Chen; Yu-Ying Chen; Ya-Ling Yeh; Ching-Ping Chang; Chien-Cheng Huang; How-Ran Guo; Ying-Jan Wang (Archives of Toxicology, 2021)

Cotton seedling drought tolerance is improved via salt preconditioning - Rong Fan; Xiujuan Su; Yaping Guo; Fenglei Sun; Yanying Qu; Quanjia Chen (Protoplasma, 2021)

Accumulation and Depuration of Cd and its Effect on the Expressions of Metallothionein and Apoptotic Genes in Litopenaeus vannamei - Ling Li; Yu-Chun Shen; Jin-Rong Liang; Hu Liu; Tian-Ci Chen; Hui Guo (Bulletin of Environmental Contamination and Toxicology, 2021)

Retraction Note to: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-qian Guo; Yu Chen; Bai-bing Mi; Shao-nong Dang; Dou-dou Zhao; Rong Liu; Hong-li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2020)

Crosstalk between PKC and MAPK pathway activation in cardiac fibroblasts in a rat model of atrial fibrillation - Wei-hua Guo; Xian Wang; Mei-sheng Shang; Zhe Chen; Qi Guo; Li Li; Hai-ying Wang; Rong-hui Yu; Chang-sheng Ma (Biotechnology Letters, 2020)

Microalgae for saline wastewater treatment: a critical review - Hoang Nhat Phong Vo; Huu Hao Ngo; Wenshan Guo; Soon Woong Chang; Dinh Duc Nguyen; Zhuo Chen; Xiaochang C. Wang; Rong Chen; Xinbo Zhang (Critical Reviews in Environmental Science and Technology, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Responses of Cloud-Radiative Forcing to Strong El Niño Events over the Western Pacific Warm Pool as Simulated by CAMS-CSM - Baichao Zhang; Zhun Guo; Xiaolong Chen; Tianjun Zhou; Xinyao Rong; Jian Li (Journal of Meteorological Research, 2020)

Simulating Spatial Variation of Soil Carbon Content in the Yellow River Delta: Comparative Analysis of Two Artificial Neural Network Models - Chen Wang; Yuan Cui; Ziwen Ma; Yutong Guo; Qian Wang; Yujiao Xiu; Rong Xiao; Mingxiang Zhang (Wetlands, 2020)

Do arbuscular mycorrhizal fungi help the native species Bidens biternata resist the invasion of Bidens alba? - Jun-Kang Cheng; Mao-Feng Yue; Heng-Rong Yang; Bao-Ming Chen; Guo-Rong Xin (Plant and Soil, 2019)

Degradation of Bisphenol S by a Bacterial Consortium Enriched from River Sediments - Xingwang Wang; Jianqiu Chen; Rong Ji; Yanhua Liu; Yu Su; Ruixin Guo (Bulletin of Environmental Contamination and Toxicology, 2019)

Predicting trait-like individual differences in fear of pain in the healthy state using gray matter volume - Xiaowan Wang; Chris Baeken; Mengxia Fang; Jiang Qiu; Hong Chen; Guo-Rong Wu (Brain Imaging and Behavior, 2019)

Nitrogen use-inefficient oilseed rape genotypes exhibit stronger growth potency during the vegetative growth stage - Xiao Guo; Huiying He; Rong An; Yuying Zhang; Rui Yang; Lanqin Cao; Xiaoming Wu; Biyun Chen; Hui Tian; Yajun Gao (Acta Physiologiae Plantarum, 2019)

Skin test of tuberculin purified protein derivatives with a dissolving microneedle-array patch - Wei Wang; Hou Ming Liu; Jing Zhou; Yu Guang Wang; Xi Feng; Hao Tang; Qinying Yan; Rong Sheng Zhu; Yu Wei Wu; Xing Guo Wang; Dan He; Fan Chen (Drug Delivery and Translational Research, 2019)

Abnormal dynamics of functional connectivity density in children with benign epilepsy with centrotemporal spikes - Rong Li; Liangcheng Wang; Heng Chen; Xiaonan Guo; Wei Liao; Ye-Lei Tang; Huafu Chen (Brain Imaging and Behavior, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

New pyrazinoquinazoline alkaloids Isolated from a culture of Stenotrophomonas maltophilia QB-77 - Sheng-Yan Qian; Cai-Ling Yang; Afsar Khan; Rong-Xiang Chen; Ming-Song Wu; Li Tuo; Qian Wang; Jian-Guo Liu; Gui-Guang Cheng (Natural Product Research, 2019)

Two new benzophenones and one new natural amide alkaloid isolated from a mangrove-derived Fungus Penicillium citrinum - Cai-Juan Zheng; Hai-Xia Liao; Rong-Qing Mei; Guo-Lei Huang; Lu-Jia Yang; Xue-Ming Zhou; Tai-Ming Shao; Guang-Ying Chen; Chang-Yun Wang (Natural Product Research, 2019)

RETRACTED ARTICLE: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-Qian Guo; Yu Chen; Bai-Bing Mi; Shao-Nong Dang; Dou-Dou Zhao; Rong Liu; Hong-Li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2019)

Climate Sensitivity and Feedbacks of a New Coupled Model CAMS-CSM to Idealized CO2 Forcing: A Comparison with CMIP5 Models - Xiaolong Chen; Zhun Guo; Tianjun Zhou; Jian Li; Xinyao Rong; Yufei Xin; Haoming Chen; Jingzhi Su (Journal of Meteorological Research, 2019)

An Assessment of ENSO Stability in CAMS Climate System Model Simulations - Lijuan Hua; Lin Chen; Xinyao Rong; Jian Li; Guo Zhang; Lu Wang (Journal of Meteorological Research, 2019)

A new benzofuran from the heartwood of Dalbergia latifolia - Rong-Hua Liu; Dan-Yi Mei; Shuai Lin; Ding-Qing Wang; Feng Shao; Lan-Ying Chen; Shan-Liang Guo (Natural Product Research, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

A Longitudinal Functional Magnetic Resonance Imaging Study of Working Memory in Patients Following a Transient Ischemic Attack: A Preliminary Study - Wei Su; Jian Guo; Yun Zhang; Jie Zhou; Ning Chen; Muke Zhou; Rong Li; Huafu Chen; Li He (Neuroscience Bulletin, 2018)

Nutrient Balancing by Captive Golden Snub-Nosed Monkeys (Rhinopithecus roxellana) - Stephanie T. Chen; Xi Luo; Rong Hou; David Raubenheimer; Weihong Ji; Xuelin Jin; Zhi Jiang; Xuewei Yu; Jiajia Wang; Min Li; Songtao Guo; Baoguo Li (International Journal of Primatology, 2018)

The CAMS Climate System Model and a Basic Evaluation of Its Climatology and Climate Variability Simulation - Xinyao Rong; Jian Li; Haoming Chen; Yufei Xin; Jingzhi Su; Lijuan Hua; Tianjun Zhou; Yanjun Qi; Zhengqiu Zhang; Guo Zhang; Jianduo Li (Journal of Meteorological Research, 2018)

An Assessment of CAMS-CSM in Simulating Land–Atmosphere Heat and Water Exchanges - Guo Zhang; Jianduo Li; Xinyao Rong; Yufei Xin; Jian Li; Haoming Chen; Jingzhi Su; Lijuan Hua (Journal of Meteorological Research, 2018)

Plant-mediated competition facilitates a phoretic association between a gall mite and a psyllid vector - Jianling Li; Sai Liu; Kun Guo; Fan Zhang; Haili Qiao; Jianmin Chen; Mengke Yang; Xiu Zhu; Rong Xu; Changqing Xu; Jun Chen (Experimental and Applied Acarology, 2018)

Agrobacterium tumefaciens-mediated transformation system for the important medicinal plant Dendrobium catenatum Lindl - Ji Chen; Li Wang; Jianbin Chen; Jin Huang; Fan Liu; Rong Guo; Li Yang; Aby Grabon; Ke Zhao; Fanlei Kong; Chen Liu; Mengliang Tian (In Vitro Cellular & Developmental Biology - Plant, 2018)

AMPKα inactivation destabilizes atherosclerotic plaque in streptozotocin-induced diabetic mice through AP-2α/miRNA-124 axis - Wen-Jing Liang; Sheng-Nan Zhou; Mei-Rong Shan; Xue-Qin Wang; Miao Zhang; Yuan Chen; Yun Zhang; Shuang-Xi Wang; Tao Guo (Journal of Molecular Medicine, 2018)

Genetic diversity and population structure of the northern snakehead (Channa argus Channidae: Teleostei) in central China: implications for conservation and management - Ruo-Jin Yan; Gui-Rong Zhang; Xiang-Zhao Guo; Wei Ji; Kun-Ci Chen; Gui-Wei Zou; Kai-Jian Wei; Jonathan P. A. Gardner (Conservation Genetics, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Ionizing Radiation Blocks Hair Cell Regeneration in Zebrafish Lateral Line Neuromasts by Preventing Wnt Signaling - Rong Li; Guixiang Liao; Guo Yin; Baiyao Wang; Miaohong Yan; Xiaoshan Lin; Wenqing Zhang; Xiaohui Chen; Shasha Du; Yawei Yuan (Molecular Neurobiology, 2018)

Design, synthesis and biological evaluation of phenylpicolinamide sorafenib derivatives as antitumor agents - Chunjiang Wu; Shan Xu; Yuping Guo; Jielian Wu; Rong Luo; Wenhui Wang; Yuanbiao Tu; Le Chen; Wufu Zhu; Pengwu Zheng (Medicinal Chemistry Research, 2018)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Attenuation of β-Amyloid Toxicity In Vitro and In Vivo by Accelerated Aggregation - Aihua Yang; Chenxuan Wang; Baomin Song; Wendi Zhang; Yuanyuan Guo; Rong Yang; Guangjun Nie; Yanlian Yang; Chen Wang (Neuroscience Bulletin, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Eudragit S100-Coated Chitosan Nanoparticles Co-loading Tat for Enhanced Oral Colon Absorption of Insulin - Shuangxi Chen; Feng Guo; Tiantian Deng; Siqi Zhu; Wenyu Liu; Haijun Zhong; Hua Yu; Rong Luo; Zeyuan Deng (AAPS PharmSciTech, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Heat shock protein 70 inhibits cardiomyocyte necroptosis through repressing autophagy in myocardial ischemia/reperfusion injury - Xiaojuan Liu; Chao Zhang; Chi Zhang; Jingjing Li; Wanwan Guo; Daliang Yan; Chen Yang; Jianhua Zhao; Tian Xia; Yuqing Wang; Rong Xu; Xiang Wu; et al. (In Vitro Cellular & Developmental Biology - Animal, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Downregulation of ubiquitin-specific protease 14 (USP14) inhibits breast cancer cell proliferation and metastasis, but promotes apoptosis - Lianxin Zhu; Shuyun Yang; Song He; Fulin Qiang; Jing Cai; Rong Liu; Changjiang Gu; Zengya Guo; Chen Wang; Wei Zhang; Chunhui Zhang; Yingying Wang (Journal of Molecular Histology, 2016)

Effects of silica exposure on the cardiac and renal inflammatory and fibrotic response and the antagonistic role of interleukin-1 beta in C57BL/6 mice - Jiali Guo; Tingming Shi; Xiuqing Cui; Yi Rong; Ting Zhou; Zhihong Zhang; Yuewei Liu; Yan Shen; Weihong Chen (Archives of Toxicology, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

Paenibacillus populi sp. nov., a novel bacterium isolated from the rhizosphere of Populus alba - Tong-Yan Han; Xiao-Mei Tong; Yan-Wei Wang; Hui-Min Wang; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Genetic diversity revealed by morphological traits and ISSR markers in 48 Okras (Abelmoschus escullentus L.) - Cong-Ying Yuan; Ping Wang; Pang-Pang Chen; Wen-Jun Xiao; Cheng Zhang; Shuai Hu; Ping Zhou; Hong-Ping Chang; Zhuang He; Rong Hu; Xiu-Tao Lu; Jia-Zhuo Ye; et al. (Physiology and Molecular Biology of Plants, 2015)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Paenibacillus vini sp. nov., isolated from alcohol fermentation pit mud in Sichuan Province, China - Xiao-Rong Chen; Cheng-Bin Shao; Yan-Wei Wang; Ming-Xiong He; Ke-Dong Ma; Hui-Min Wang; De-Long Kong; Xiang Guo; Yi-Qing Zhou; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

Transformation of the endophytic fungus Acremonium implicatum with GFP and evaluation of its biocontrol effect against Meloidogyne incognita - Yu-Rong Yao; Xue-Liang Tian; Bao-Ming Shen; Zhen-Chuan Mao; Guo-hua Chen; Bing-Yan Xie (World Journal of Microbiology and Biotechnology, 2015)

Association analyses of FGFR2 gene polymorphisms with femoral neck bone mineral density in Chinese Han population - Shan-Shan Dong; Tie-Lin Yang; Han Yan; Zheng-Qin Rong; Jia-Bin Chen; Ruo-Han Hao; Xiao-Feng Chen; Yan Guo (Molecular Genetics and Genomics, 2015)

Removal of antibiotics and antibiotic resistance genes in rural wastewater by an integrated constructed wetland - Jun Chen; You-Sheng Liu; Hao-Chang Su; Guang-Guo Ying; Feng Liu; Shuang-Shuang Liu; Liang-Ying He; Zhi-Feng Chen; Yong-Qiang Yang; Fan-Rong Chen (Environmental Science and Pollution Research, 2015)

Fibroblast Growth Factor 4 Is Required but not Sufficient for the Astrocyte Dedifferentiation - Guo-Dong Feng; Bao-Rong He; Fan Lu; Lin-Hong Liu; Lingling Zhang; Bo Chen; Zu-Ping He; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Impact of anthropogenic activities on urban stream water quality: a case study in Guangzhou, China - Jin-Song Liu; Ling-Chuan Guo; Xian-Lin Luo; Fan-Rong Chen; Eddy Y. Zeng (Environmental Science and Pollution Research, 2014)

Characterization and molecular mapping of stripe rust resistance gene Yr61 in winter wheat cultivar Pindong 34 - X. L. Zhou; D. J. Han; X. M. Chen; H. L. Gou; S. J. Guo; L. Rong; Q. L. Wang; L. L. Huang; Z. S. Kang (Theoretical and Applied Genetics, 2014)

The rescuable function and mechanism of resveratrol on As2O3-induced hERG K+ channel deficiency - Xin Zhao; Kai-ping Zhang; Ting Huang; Cai-Chuan Yan; Li-Rong Liu; Qi-Lei Zhu; Feng-Feng Guo; Chen Liu; Bao-Xin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

TNF-α, IL-6, and Leptin Increase the Expression of miR-378, an Adipogenesis-Related microRNA in Human Adipocytes - Lu-lian Xu; Chun-mei Shi; Guang-feng Xu; Ling Chen; Ling-ling Zhu; Lu Zhu; Xi-rong Guo; Mei-yu Xu; Chen-bo Ji (Cell Biochemistry and Biophysics, 2014)

Analysis on the association between PPARα/γ polymorphisms and lipoprotein(a) in a Chinese Han population - Hui-Jian Xie; Bo Hai; Ming Wu; Qiu Chen; Meng-Meng Liu; Chen Dong; Zhi-Rong Guo (Molecular Genetics and Genomics, 2014)

The cellular community in the intestine of the shrimp Penaeus penicillatus and its culture environments - Chun-zhong Wang; Guo-rong Lin; Tao Yan; Zhi-peng Zheng; Bin Chen; Fu-lin Sun (Fisheries Science, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

Isolation and characterization of nineteen novel polymorphic microsatellite loci for the northern snakehead Channa argus - Ruo-Jin Yan; Kai-Jian Wei; Xiang-Zhao Guo; Gui-Rong Zhang; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Conservation Genetics Resources, 2014)

Two new bicyclic sesquiterpenes from the stems of Kadsura heteroclita - Wei Su; Jian-Ping Zhao; Jian Hu; Min Yang; Melissa Jacob; Xiong Cai; Rong Zeng; Sheng-Huang Chen; Hui-Yong Huang; Ikhlas Khan; De-An Guo; Wei Wang (Natural Product Research, 2014)

Electrosprayed Microparticles with Loaded pDNA-Calcium Phosphate Nanoparticles to Promote the Regeneration of Mature Blood Vessels - Xueqin Guo; Tian Xia; Huan Wang; Fang Chen; Rong Cheng; Xiaoming Luo; Xiaohong Li (Pharmaceutical Research, 2014)

Association between melatonin receptor 1A (MTNR1A) gene single-nucleotide polymorphisms and the velvet antler yield of Sika deer - Fei-Fei Yang; Li-Jun Huo; Li-Guo Yang; Hasan Riaz; Li-Rong Xiong; Jian-Guo Chen; Shu-Jun Zhang; Jia-Jun Xiong (Molecular Biology Reports, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Estrogen receptor α gene PvuII polymorphism and coronary artery disease: a meta-analysis of 21 studies - Jie Ding; Hui Xu; Xiang Yin; Fu-rong Zhang; Xiao-ping Pan; Yi-an Gu; Jun-zhu Chen; Xiao-gang Guo (Journal of Zhejiang University-SCIENCE B, 2014)

MiR-335, an Adipogenesis-Related MicroRNA, is Involved in Adipose Tissue Inflammation - Lu Zhu; Ling Chen; Chun-Mei Shi; Guang-Feng Xu; Lu-Lian Xu; Ling-Ling Zhu; Xi-Rong Guo; Yuhui Ni; Yan Cui; Chenbo Ji (Cell Biochemistry and Biophysics, 2014)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

Characteristics of rainfall erosivity based on tropical rainfall measuring mission data in Tibet, China - Jian-rong Fan; Yang Chen; Dong Yan; Fen-fen Guo (Journal of Mountain Science, 2013)

Characterization of microRNA expression profiles in 3T3-L1 adipocytes overexpressing C10orf116 - Jie Qiu; Xiao-guang Zhou; Xiao-yu Zhou; Chun Zhu; Chun-mei Shi; Chen-bo Ji; Rui Cheng; Yong Li; Xi-rong Guo (Molecular Biology Reports, 2013)

Neutralization of interleukin-1 beta attenuates silica-induced lung inflammation and fibrosis in C57BL/6 mice - Jiali Guo; Nali Gu; Jie Chen; Tingming Shi; Yun Zhou; Yi Rong; Ting Zhou; Wenxiang Yang; Xiuqing Cui; Weihong Chen (Archives of Toxicology, 2013)

Identification of miR-221 and -222 as important regulators in genotype IV swine hepatitis E virus ORF3-expressing HEK 293 cells - Ying Cheng; Li Du; Qiaoyun Shi; Hanwei Jiao; Xiaoru Zhang; Yongchang Hao; Hui Rong; Jianing Zhang; Xiaoxiao Jia; Shiyu Guo; Wenhua Kuang; Hui Zhang; et al. (Virus Genes, 2013)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Comparison of metabolic effects of ziprasidone versus olanzapine treatment in patients with first-episode schizophrenia - Jian-Jun Ou; Yi Xu; Hong-Hui Chen; Xiaoduo Fan; Keming Gao; Juan Wang; Xiao-Feng Guo; Ren-Rong Wu; Jing-Ping Zhao (Psychopharmacology, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Genotype and haplotype analysis of the AZGP1 gene in cattle - Bao Zhang; Yi Kun Guo; Shengbin Li; Liang Zhi Zhang; Xian Yong Lan; Shen Rong Hu; Hong Chen (Molecular Biology Reports, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Repeated administration of berberine inhibits cytochromes P450 in humans - Ying Guo; Yao Chen; Zhi-rong Tan; Curtis D. Klaassen; Hong-hao Zhou (European Journal of Clinical Pharmacology, 2012)

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

Erratum to: Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Synthesis of novel 6-triazologlycolipids via click chemistry and their preliminary cytotoxicity assessments - Hai-Lin Zhang; Xiao-Peng He; Li Sheng; Yuan Yao; Wei Zhang; Xiao-Xin Shi; Jia Li; Guo-Rong Chen (Molecular Diversity, 2011)

Usefulness of Enhanced Power Doppler Imaging in Monitoring Acral Microcirculation in Type 2 Diabetes Mellitus and its Complications - Fang Ma; Baozhen Zhao; Huiping Zhang; Wei-Ping Li; Yuan-Yuan Liu; Yuan-Yuan Dang; Rong Wu; Le Hang Guo; Chen Lu (Cell Biochemistry and Biophysics, 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Overexpression of PGC-1β improves insulin sensitivity and mitochondrial function in 3T3-L1 adipocytes - Chun-Lin Gao; Guang-Ling Liu; Shi Liu; Xiao-Hui Chen; Chen-Bo Ji; Chun-Mei Zhang; Zheng-Kun Xia; Xi-rong Guo (Molecular and Cellular Biochemistry, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

A Proteomic Investigation of B Lymphocytes in an Autistic Family: A Pilot Study of Exposure to Natural Rubber Latex (NRL) May Lead to Autism - Chen Shen; Xin-liang Zhao; Weina Ju; Xiao-bing Zou; Li-rong Huo; Wu Yan; Jun-hua Zou; Guo-di Yan; Edmund C. Jenkins; W. Ted Brown; Nanbert Zhong (Journal of Molecular Neuroscience, 2011)

Construction of a Tn5-Tagged Mutant Library of Xanthomonas oryzae pv. oryzicola as An Invaluable Resource for Functional Genomics - Hua-Song Zou; Liang Yuan; Wei Guo; Yu-Rong Li; Yi-Zhou Che; Li-Fang Zou; Gong-You Chen (Current Microbiology, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

Prognostic value of serum soluble Fas in patients with locally advanced unresectable rectal cancer receiving concurrent chemoradiotherapy - Qi-lian Liang; Zhou-yu Li; Guo-qiang Chen; Zhen-nan Lai; Bi-rong Wang; Jie Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

Effects of erythromycin on voriconazole pharmacokinetics and association with CYP2C19 polymorphism - Hui-Yan Shi; Jin Yan; Wen-Hui Zhu; Guo-Ping Yang; Zhi-Rong Tan; Wei-Hua Wu; Gan Zhou; Xiao-Ping Chen; Dong-Sheng Ouyang (European Journal of Clinical Pharmacology, 2010)

A new hexenol glycoside from leaves of Smallanthus sonchifolius - Xiang Zheng; Gai Kuo; Dou De-Qiang; Chen Gui-Rong; Kang Ting-Guo; Shi Yu-Yuan; Li Xing-Tai; Dong Feng (Natural Product Research, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Diversity and Antimicrobial and Plant-Growth-Promoting Activities of Endophytic Fungi in Dendrobium loddigesii Rolfe - Xiao Mei Chen; Hai Ling Dong; Ke Xing Hu; Zhi Rong Sun; Juan Chen; Shun Xing Guo (Journal of Plant Growth Regulation, 2010)

A preliminary study of the Six-Item Screener in detecting cognitive impairment - Mei-Rong Chen; Qi-Hao Guo; Xin-Yi Cao; Zhen Hong; Xiao-Hong Liu (Neuroscience Bulletin, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Gene expression profiles in the prefrontal cortex of SHR rats by cDNA microarrays - Jie Qiu; Qin Hong; Rong-hua Chen; Mei-ling Tong; Min Zhang; Li Fei; Xiao-qin Pan; Mei Guo; Xi-rong Guo; Xia Chi (Molecular Biology Reports, 2010)

Identification of QTLs for yield and yield components of barley under different growth conditions - Da-wei Xue; Mei-xue Zhou; Xiao-qin Zhang; Song Chen; Kang Wei; Fan-rong Zeng; Ying Mao; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Effect of silymarin on the pharmacokinetics of losartan and its active metabolite E-3174 in healthy Chinese volunteers - Yang Han; Dong Guo; Yao Chen; Yu Chen; Zhi-Rong Tan; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Effect of the untranslated region and signal peptide sequence of the insecticidal gene from Pseudomonas pseudoalcaligenes on the activity of its expression products in tobacco - Min Huang; Da-Xu Li; Wen-Liang Xiang; Hao Chen; Jian-Hua Guo; Jian Zhao; Jie Zhang; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Identification of the tree shrew ATP-binding cassette transporter A1 (ABCA1) and its expression in tissues - Wu-Wei Zeng; Bing Zhou; Hui-Rong Liu; Guo-Tao Sun; Bao-Sheng Chen (Molecular Biology Reports, 2009)

The CYP2C19 ultra-rapid metabolizer genotype influences the pharmacokinetics of voriconazole in healthy male volunteers - Guo Wang; He-Ping Lei; Zhi Li; Zhi-Rong Tan; Dong Guo; Lan Fan; Yao Chen; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Isolation and identification of Sclerotinia stem rot causal pathogen in Arabidopsis thaliana - Ai-rong Wang; Wen-wei Lin; Xiao-ting Chen; Guo-dong Lu; Jie Zhou; Zong-hua Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Expression, purification and characterization of a phyA m -phyCs fusion phytase - Li-kou Zou; Hong-ning Wang; Xin Pan; Guo-bao Tian; Zi-wen Xie; Qi Wu; Hui Chen; Tao Xie; Zhi-rong Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Characterization of high-yield performance as affected by genotype and environment in rice - Song Chen; Fang-rong Zeng; Zong-zhi Pao; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2008)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Thrombin-induced microglial activation contributes to the degeneration of nigral dopaminergic neurons in vivo - Cheng-Fang Huang; Gang Li; Rong Ma; Sheng-Gang Sun; Jian-Guo Chen (Neuroscience Bulletin, 2008)

Associations between arbuscular mycorrhizal fungi and Rhynchrelyrum repens in abandoned quarries in southern China - Yan Chen; Jian-gang Yuan; Zhong-yi Yang; Guo-rong Xin; Ling Fan (Plant and Soil, 2008)

Polymorphisms in intron 1 of the porcinePOU1F1 gene - Cheng-Yi Song; Bo Gao; Shang-Hui Teng; Xiao-Yang Wang; Fei Xie; Guo-hong Chen; Zhi-Yue Wang; Rong-bin Jing; Jiu-De Mao (Journal of Applied Genetics, 2007)

Abundant genetic diversity in cultivated Codonopsis pilosula populations revealed by RAPD polymorphisms - Hong Bo Guo; Bao Rong Lu; Qian Hong Wu; Jia Kuan Chen; Tong Shui Zhou (Genetic Resources and Crop Evolution, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)